Mobile Application Balance B.M.S (Body, Mind, Soul) - Ainul Dhabitah Mohammad Zainal; Wan Shazlina Wan Shazlina (Journal of Computing Technologies and Creative Content, 2022)
When it comes to mobile applications, they are computer programmes or software applications that can run on any operating system or any mobile device. As a result of the lockdown, people now have a more complicated relationship with food to maintain a healthy lifestyle. Their eating habits and emotional well-being have also been influenced by working from home, resulting in less physical activity. The vast majority of people are entirely unaware of the numerous advantages of Herbalife products. According to this study, Adobe Animate will be utilised to develop a mobile application that teaches the proper way to eat healthfully and maintain a healthy B.M.S balance (Body, Mind, Soul). This method focuses on the nutritional balance of every meal. Using Herbalife products as a meal replacement helps them gain a more comprehensive understanding of what it means to live an active and healthy lifestyle. As a result, the goal of this study is to determine the most effective way for people to train balance by eating a healthy lifestyle. To assess the effectiveness of the mobile application for the balance of B.M.S. (Body, Mind, and Soul), the development application used Herbalife products in conjunction with a mobile application that was developed to promote B.M.S. (Body, Mind, Soul). The ADDIE MODEL was utilised in the current study (Analysis, Design, Development, Implementation, and Evaluation). As a result, this research will aid in improving the effectiveness of mobile applications to balance people who require proper meal replacement with Herbalife products can benefit from the B.M.S (Body, Mind, and Soul) programme, which is available through the development of the mobile application.